Producción de Lactuca sativa var. crispa L. a partir de diferentes dosis de fertilización orgánica - Rivaldi, Noelia Mariana (2024)
Lettuce (Lactuca sativa L.) is the most consumed leafy vegetable in Argentina, primarily grown in peri-urban green belts near mass fresh consumption markets. Due to the high economic and environmental costs of mineral fertilizers, alternatives such as the incorporation of organic amendments are being explored to meet crop nutrient needs. However, studies on the performance of these products and their impact on lettuce growth rates are limited, posing a challenge for the development of local agroecological practices. The aim of this study was to evaluate the effect of different doses of organic fertilization on the growth of lettuce cultivars in two different seasons. Four doses of organic fertilizer, aimed to supply 0, 50, 100, and 150 kg N ha⁻¹, were applied in combination with the cultivars Waldman Green and Isabella in spring- summer, and Brisa and Isabella in autumn-winter. Two 4x2 factorial experiments were conducted using a completely randomized block design, with four replicates in spring-summer and three replicates in autumn-winter. Samples from three contiguous lettuce plants per experimental unit were taken at 14, 28, and 48 days after transplanting in spring-summer, and at 14, 27, 42, and 57 days after transplanting in autumn-winter. Measurements included dry matter accumulation, absolute growth rate (AGR), relative growth rate (RGR), net assimilation rate (NAR), leaf area (LA), and nutrient residue analysis of the entire plant in the laboratory. The significance of treatments on the measured variables was analyzed, along with the factors and interaction between organic fertilizer doses and cultivar. The homogeneity of variances and normality of residuals were verified. In cases of significant interaction, regression analysis by cultivar was performed. In the absence of significant interaction, doses were analyzed using regression analysis and cultivars using Tukey's test, with a significance level of 5%. While no significant differences in organic fertilizer doses were observed on growth rates in the first trial, the second trial revealed statistical differences in doses and cultivars. However, plants showed greater dry matter accumulation and higher growth rates during spring-summer compared to autumn-winter.